The Impact of Generative AI on Digital Empathy and Human Emotional Understanding in Online Communication - Satria, Aruna; Gita, Cahya; Dewangga, Dewangga (Journal Social Humanity Perspective, 2025)
This study investigates how generative artificial intelligence (AI) influences human emotional understanding and digital empathy in online communication contexts. Grounded in social psychology and management theory, it examines whether emotionally responsive AI can enhance individuals’ empathic engagement and emotional comprehension during mediated interactions. Employing a quantitative research design, data were collected from participants who engaged in text-based communication with either emotionally expressive or neutral AI systems. Statistical analyses, including t-tests and correlation models, revealed that exposure to emotionally responsive AI significantly increased users’ empathy levels and emotional understanding compared to neutral AI interaction. These findings extend existing theories of emotional intelligence and digital communication by demonstrating that empathy is not solely a human trait but a relational dynamic co-constructed between human and algorithmic agents. From a management perspective, the results suggest that emotional AI can function as a strategic capability enhancing leadership communication, organizational culture, and customer experience through affective augmentation. However, the study also underscores ethical considerations surrounding authenticity, emotional manipulation, and governance in the deployment of affective technologies. Ultimately, this research argues that digital empathy represents a pivotal competency for the future of organizational management, requiring a balance between technological innovation and human-centered ethics. It contributes to the emerging discourse on emotionally intelligent systems and calls for managerial frameworks that foster authentic, ethical, and emotionally sustainable human AI collaboration.